Protestant legacies in nordic law: the early modern period - Rasmussen, Tarald; Sunde, Jørn Øyrehagen (Law and religion in the early modern period, 2023)
The overarching goal of the book is to examine the relations between Lutheran majority traditions and the development of secular law in the Nordic region in the early modern period, from the 16th to the 18th century. The early modern Nordic region included the kingdoms of Denmark/Norway and Sweden – with the Finnish diocese Åbo as part of the Swedish realm. Both kingdoms were consolidated as Lutheran countries after the reformation. While this change occurred in a determined and radical way in Denmark, in Sweden the transformation was more hesitant. Due to its mixed Protestant (Lutheran/Calvinist) and Roman-Catholic heritage, case studies dealing with Germany offer interesting comparative perspectives. Integral to the project is the awareness of tensions between different religious, legal and philosophical traditions in the interface between majority/minority/equality positions, including Protestant minority movements and the Eastern-Orthodox church. The authors are experts in church history and legal history from Germany, Belgium, Denmark, Sweden, Finland, and Norway